Evaluation of the potential of biocementation in clayey and sandy soils for foundations using fish viscera waste - Vilcas Ramos, Gerardo Alfredo (2025)
Faced with the dual challenges of rapid urbanization on unsuitable soils and the environmental burden of organic waste from the fishing industry, Peru urgently needs innovative and sustainable engineering solutions. A biotechnological alternative is introduced for soil improvement based on Microbial - Induced Calcite Precipitation (MICP), using Sporosarcina pasteurii bacteria nourished with nutrient - rich extracts from the viscera of horse mackerel, mullet, and bonito. Bacterial cultures were prepared in a solution of urea - ammonium, distilled water, and Tris buffer, with parameters such as bacterial concentration (1.10E7 to 1.30E7 CFU/ml), viscera extract volume (3 – 9 ml), and temperature (25 – 35 °C) optimized for maximum calcium carbonate precipitation. Under optimal conditions (1.30E7 CFU/ml, 9 ml, 35 °C), CaCO₃ production reached 0.0194 g. Soil treatment trials demonstrated significant engineering benefits: in low - plasticity clay, allowable bearing capacity increased by 80% and deformation was reduced by 68.5%; in poorly graded sand with gravel, capacity rose by 20% and deformation decreased by 35.1%. Clay - sand mixtures showed capacity gains up to 31% and deformability reductions of 55.7%. The results are attributed to the formation of calcium carbonate bridges, which enhance particle cohesion and stiffness. Technical and environmental feasibility of revalorizing fish viscera as a nutrient source for biocementation, offering a low - cost and sustainable strategy for urban soil stabilization.